Investigation of pH and Temperature Profiles in the GI Tract of Fasted Human Subjects Using the Intellicap® System - Koziolek, Mirko; Grimm, Michael; Becker, Dieter; Iordanov, Ventzeslav; Zou, Hans; Shimizu, Jeff; Wanke, Christoph; Garbacz, Grzegorz; Weitschies, Werner (Journal of pharmaceutical sciences, 2015)
Gastrointestinal (GI) pH and temperature profiles under fasted-state conditions were investigated in two studies with each 10 healthy human subjects using the IntelliCap® system. This telemetric drug delivery device enabled the determination of gastric emptying time, small bowel transit time, and colon arrival time by significant pH and temperature changes. The study results revealed high variability of GI pH and transit times. The gastric transit of IntelliCap® was characterized by high fluctuations of the pH with mean values ranging from pH 1.7 to pH 4.7. Gastric emptying was observed after 7–202min (median: 30 min). During small bowel transit, which had a duration of 67–532min (median: 247 min), pH values increased slightly from pH 5.9–6.3 in proximal parts to pH 7.4–7.8 in distal parts. Colonic pH conditions were characterized by values fluctuating mainly between pH 5 and pH 8. The pH profiles and transit times described in this work are highly relevant for the comprehension of drug delivery of solid oral dosage forms comprising ionizable drugs and excipients with pH-dependent solubility.